Problem Solving Skill Seen From Adversity Quotient on Guided Discovery Learning Model With Metacognitive Approach Assisted By Schoology - Wahyuningsih, Tri; Dwidayati, Nurkaromah; Wardono, Wardono (Universitas Negeri Semarang, 2020)
This research aims to describe problem solving process of students taught by guided discovery learning model with metacognitive approach seen from Adversity Quotient (AQ). This mixed method used sequential explanatory – an ordering combination from quantitative to qualitative. The population consisted of all VIII Junior High School 13 Semarang. The sample was taken by random sampling. This research showed that GDL with metacognitive approach and assisted by Schoology was effective to problem solving skill. Furthermore, the description of problem solving skill seen from AQ was varied. It was shown by 19 students categorized climber – 13 of them were categorized high problem solving skill students, 4 moderate level students, and 2 poor level students. The camper category students consisted of 14 students – 12 of them were categorized high problem solving skill students, 2 moderate level students, and none of them was categorized poor level stuent. The quitter category students consisted of the persons – none of them was categorized high but each one of them was categorized into moderate and poor level student.